Patterns of non-employment, and of disadvantage, in a recession - Richard Berthoud (University of Essex, Institute for Social and Economic Research (ISER), 2009)
This short paper aims to contribute to the live debate about the current recession in the United Kingdom by analysing the impact of the recessions of the early 1980s and 1990s on non-employment patterns among people in the main range of working ages. The implication is that the effects observed in earlier business cycles are likely to be repeated now. The paper shows the impact of cyclical factors on overall patterns of non-employment and which social groups are most affected. A key question is whether types of people who are already disadvantaged are especially sensitive to a down-turn.
Keywords: 330